Kompensasi, Pelatihan, Dan Disiplin Kerja Terhadap Kinerja Karyawan - Amaliya, Resty (PERFECT EDUCATION FAIRY, 2024)
The purpose of this research is to analyze both partially and simultaneously the effect of reward, punishment, and motivation on employee performance in private educational institutions in South Tangerang City. The research method applied is quantitative with a sample of 45 employees from several private schools. The findings indicate that rewards have a positive and significant effect on employee performance, as proven through the partial t-test (tcount 2.172 > ttable 1.68195). Punishment also has a positive and significant effect on employee performance, supported by a significant level of 0.000 < 0.05 and tcount 4.396 > ttable 1.68195. Motivation likewise shows a positive and significant impact on performance, indicated by tcount 5.994 > ttable 1.68195 and significance level of 0.000. Furthermore, reward, punishment, and motivation simultaneously exert a positive and significant effect on employee performance, as evidenced by Fcount 76.473 > Ftable 2.83 and significance value 0.000 < 0.05.